Causal mechanism in social network sites under consideration of the social capital theory - Sander, Tom; Teh, Phoey Lee * (Óbuda University, Keleti Faculty of Business and Management, 2014)
The paper gives a theoretical framework for social capital theory under the consideration of social media. Three components exist to explain the causal mechanism in social network sites under the consideration of the social capital theory, which is the technological design, institutional design and the process design. Additionally, it is mentioned that social network sites creates social capital and social capital enables social network sites to be beneficial for the member of virtual networks. The limitation of the paper is the absence of empirical confirmation at the moment but it illustrates the empirical construct to test the existence of social capital in social network sites. The objective of the paper is to describe the framework of social capital theory under the consideration of virtual networks. That provides an insight in the development of social network sites, besides giving the frame to explain changes in social network sites and the behaviour of individuals and processes.